2011
DOI: 10.2337/db10-0705
|View full text |Cite
|
Sign up to set email alerts
|

Differential Lipid Partitioning Between Adipocytes and Tissue Macrophages Modulates Macrophage Lipotoxicity and M2/M1 Polarization in Obese Mice

Abstract: OBJECTIVEObesity-associated insulin resistance is characterized by a state of chronic, low-grade inflammation that is associated with the accumulation of M1 proinflammatory macrophages in adipose tissue. Although different evidence explains the mechanisms linking the expansion of adipose tissue and adipose tissue macrophage (ATM) polarization, in the current study we investigated the concept of lipid-induced toxicity as the pathogenic link that could explain the trigger of this response.RESEARCH DESIGN AND MET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
282
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(303 citation statements)
references
References 29 publications
17
282
1
3
Order By: Relevance
“…Along with this hypothesis, in vivo impairment of FA catabolism in ATMs that have accumulated lipids has systemic and local consequences [45]. However, long term lipid accumulation in ATMs promotes M1 polarisation and AT inflammation [46]. Together, these results suggest there is no association between fat cell lipolysisderived FA uptake and subsequent storage as TAGs in ATMs and the induction of inflammatory pathways.…”
Section: Discussionmentioning
confidence: 56%
“…Along with this hypothesis, in vivo impairment of FA catabolism in ATMs that have accumulated lipids has systemic and local consequences [45]. However, long term lipid accumulation in ATMs promotes M1 polarisation and AT inflammation [46]. Together, these results suggest there is no association between fat cell lipolysisderived FA uptake and subsequent storage as TAGs in ATMs and the induction of inflammatory pathways.…”
Section: Discussionmentioning
confidence: 56%
“…This is consistent with the observed more proinflammatory state in EAT than in MAT and with the increased MCP-1 mRNA levels in VAT upon both high-fat diets. In addition, the high CD11c expression in EAT from HF/n-3 mice could indicate that ATM are predominantly of the classical activated M1 state (54) and/or that the number of other dendritic immune cells belonging to the cell family of mononuclear phagocytes (27) increased simultaneously. This consideration may apply partly to MAT from obese HF/n-3 mice.…”
Section: Discussionmentioning
confidence: 99%
“…This is often associated with a switch in polarization of ATM from an anti-inflammatory M2 state to a proinflammatory M1 state (37,38), possibly caused by processes involving macrophage lipotoxity (54). M1 macrophages accumulate preferentially around dead adipocytes, thereby forming necrotic CLS, whereas M2 macrophages are associated with adipose tissue remodeling and repair processes (10,38).…”
Section: Discussionmentioning
confidence: 99%
“…The adipose tissue 'expandability hypothesis' postulates that adipose tissue loses its ability to adequately store excess fat resulting in lipid spill over which promotes ectopic lipid accumulation and inflammation in macrophages (69,77). Transcriptional profile analysis of adipocytes and ATM from leptin-deficient (ob/ob) mice, demonstrated that increasing adiposity was associated with a reduction in lipogenic, lipid uptake and lipid storage gene expression in adipocytes but up-regulation in ATM.…”
Section: Fatty Acids and Adipose Tissue Macrophage Polarisationmentioning
confidence: 99%